Availability, nutritional quality, and ecological labeling of animal-based products and plant-based analogues in Brazil - Santos, Eliana de Souza Marques dos; Chávez, Davy William Hildalgo; Ayres, Ellen Mayra Menezes (Semina: Ciências Agrárias, 2026)
This study assessed the availability, nutritional quality, and economic accessibility of eco-labeled animal-based products and plant-based analogues within the urban food environment. A cross-sectional audit of 149 retail establishments in the city of Rio de Janeiro, Brazil, was conducted between July 2022 and June 2023, stratified by the Social Progress Index (Índice de Progresso Social - IPS). In total, 1,643 eco-labeled protein-rich foods (animal-based products and plant-based analogues) were evaluated for availability, price, and macronutrient composition. Multivariate factor analysis (MFA) and principal component analysis (PCA) were used to examine the relationships between product availability, geographic regions, and IPS levels, while chi-square and G tests compared product categories (p ≤ 0.05). The results indicated that IPS accounted for 86.8% of the variance in product availability, suggesting that socio-spatial segregation is strongly associated with differences in access to sustainable protein-rich foods. Plant-based products were on average 71% more expensive than their animal-based counterparts. Among plant-based products, burgers emerged as the most prevalent item in the segment, whereas certified chicken was the most prevalent within the animal-based category. The nutritional composition of plant-based products showed advantages, including higher dietary fiber content, absence of cholesterol, and a more favorable lipid profile, but also limitations, such as lower protein content and elevated sodium levels. The unequal concentration of eco-labeled protein-rich foods reinforces disparities in access to innovative and sustainable foods. The protein transition in Brazil is unlikely to occur solely through market forces; targeted public policies will be necessary to overcome structural barriers related to price, distribution, and consumer information within sustainable food systems.